KONSEP PENDIDIKAN IBNU MASKAWAIH DAN IBNU KHALDUM - MISBAHUDDIN, MISBAHUDDIN (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2017)
The concept of Ibnu Maskawaih's education about the power and humanity of human thinking, he conclude that in humans there are three forces, they are: an-nafs al-bahimiyah (animal passions) is worse force, an-nafs as-sabu’iyah (lust beast) in the middle force, and an-nafs an-nathiqiyah (intelligent soul) is good force. His concept of moral education is the obligatory education for each individual to sharp the power and capabilities of the human. According to his concept, environment will affect the education. Then, a good environment is the environment in which there is a harmonious relationship between all the components that exist in the environment. The concept of Ibn Khaldun's education about the power and ability of human thought that he laid the ratio (reason) at its central point. With human ratio, human can think and can produce science. In the process of education, morality is very important, therefore it cannot educate in a violent manner. Therefore, his thinking challenged the environment that the environment greatly influenced the human in carrying out his social function in the midst of society.